Protocol Design and Resource Allocation for LTE-U System Utilizing Licensed and Unlicensed Bands - Weihua Wu; Qinghai Yang; Runzi Liu; Kyung Sup Kwak (IEEE Access, 2019)
LTE deployed with both licensed and unlicensed bands (LTE-U) is one of the promising approaches to meet the rapidly growing data demand in wireless networks. In this paper, both throughput and fairness for the LTE-U system are maximized by a multi-objective optimization problem. Then, a log-sum-exp approximation method is developed to convert the multi-objective optimization into a single objective optimization problem. At the same time, the tradeoff between throughput and fairness is mathematically depicted by a control parameter. To tackle the obtained single objective optimization problem, a Markov chain directed algorithm is developed to convert it into a coexistence protocol design subproblem at the MAC layer and a resource allocation subproblem at the physical layer, respectively. Then, we propose adaptive exponential backoff schemes for both the LTE-U devices and the incumbent devices on the unlicensed bands. After that, a low-complexity two-iterative optimization procedure is developed to jointly allocate the licensed and unlicensed resources of the LTE-U system. The simulation results show that our proposed coexistence protocol and resource allocation can achieve fair coexistence between the LTE-U devices and the incumbent devices on the unlicensed bands, moreover it can achieve higher throughput than the non-adaptive coexistence protocol in the unlicensed bands.